Searching for host immune-microbiome mechanisms in obsessive-compulsive disorder: A narrative literature review and future directions. (June 2021) - Troyer, Emily A.; Kohn, Jordan N.; Ecklu-Mensah, Gertrude; Aleti, Gajender; Rosenberg, David R.; Hong, Suzi
Highlights: Current literature suggests immune-microbiome signaling could be relevant to OCD. We discuss mechanisms by which gut-brain-immune axis dysfunction could underlie OCD. OCD is heterogeneous, and future microbiome investigations should take this into account. This offers to be a novel area of inquiry to further our understanding and treatment of OCD. Abstract: Obsessive-compulsive disorder (OCD) is disabling and often treatment-refractory. Host immunity and gut microbiota have bidirectional communication with each other and with the brain. Perturbations to this axis have been implicated in neuropsychiatric disorders, but immune-microbiome signaling in OCD is relatively underexplored. We review support for further pursuing such investigations in OCD, including: 1) gut microbiota has been associated with OCD, but causal pathogenic mechanisms remain unclear; 2) early environmental risk factors for OCD overlap with critical periods of immune-microbiome development; 3) OCD is associated with increased risk of immune-mediated disorders and changes in immune parameters, which are separately associated with the microbiome; and 4) gut microbiome manipulations in animal models are associated with changes in immunity and some obsessive-compulsive symptoms. Theoretical pathogenic mechanisms could include microbiota programming of cytokine production, promotion of expansion and trafficking of peripheral immune cells to the CNS, and regulation of microglial function. Immune-microbiome signaling in OCD requires further exploration, and may offer novel insights into pathogenic mechanisms and potential treatment targets for this disabling disorder.